High-strength bone cement as well as preparation method and application thereof

By using calcium phosphate bone cement with specific component proportions in rotator cuff tear repair, the problem of poor anchoring in osteoporosis patients is solved, and bone cement materials with high strength, injectability and short curing time are achieved, improving bone The binding properties of cement and bone tissue are suitable for rotator cuff repair in patients with osteoporosis.

CN119236190APending Publication Date: 2025-01-03BIOPAG (CHONGQING) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560584.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The problem of poor anchoring of existing bone cement in osteoporosis patients, especially in the repair of rotator cuff tear, existing materials such as polymethyl methacrylate (PMMA) and calcium phosphate bone cement (CPC) have insufficient mechanical properties. , poor adhesion or difficulty in removing.

Method used

Using solid-phase components hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: dihydrogen phosphate: calcium monohydrogen phosphate: specific weight ratio of calcium carbonate, matching specific liquid-phase components such as sodium chloride solution and hydroxypropylene A high-strength calcium phosphate bone cement with strong injectability, short curing time and excellent mechanical properties were prepared.

Benefits of technology

The anchor fixation strength is improved, the binding performance of the material and bone tissue is improved, the mechanical strength of bone cement is enhanced, and the needs of osteoporosis patients are adapted to the needs of patients with osteoporosis. The comprehensive performance of bone cement is further improved by optimizing the component ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117777550000031
    Figure BDA0005117777550000031
  • Figure BDA0005117777550000041
    Figure BDA0005117777550000041
  • Figure BDA0005117777550000061
    Figure BDA0005117777550000061
Patent Text Reader

Abstract

The invention relates to the technical field of bone cement, and particularly discloses high-strength bone cement as well as a preparation method and application thereof. The invention discloses high-strength bone cement. The high-strength bone cement is obtained by mixing a solid-phase component and a liquid-phase component according to a solid-to-liquid ratio of 0.3-1g / mL, the solid phase component specifically comprises the following components: hydroxyapatite, tricalcium phosphate, tetracalcium phosphate, disodium hydrogen phosphate, monocalcium phosphate monohydrate and calcium carbonate in a weight ratio of (15-25): (20-40): (10-30): (10-30): (1-10): (1-10); the liquid phase component is selected from any one or more of a sodium chloride solution, a phosphate buffer solution and a hydroxypropyl methyl cellulose solution. The invention further provides a preparation method and application of the high-strength bone cement. According to the technical scheme provided by the invention, the prepared bone cement is short in curing time and excellent in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of bone cement, and in particular to a high-strength bone cement and a preparation method and application thereof. Background Art

[0002] Rotator cuff tear is a common tendon injury, which is mainly manifested by shoulder pain, limited mobility, and reduced function, especially in the middle-aged and elderly population. Arthroscopic rotator cuff repair has become an effective solution when conservative treatment is ineffective. Currently, the widely used repair methods include the use of wire anchors made of polyetheretherketone (PEEK) material. However, for patients with osteoporosis, due to the decrease in bone quality, it is difficult for existing screws to achieve an ideal anchoring effect. The bone microstructure of osteoporotic patients, such as the number of trabeculae and cortical bones, directly affects the mechanical stability of the repair.

[0003] In order to solve the problem of poor anchoring of bone screws in osteoporotic patients, bone cement-enhanced screw technology is used clinically. Polymethyl methacrylate (PMMA), as a commonly used bone cement, performs well in strengthening the pull-out resistance of screws, but its elastic modulus is quite different from that of cancellous bone, which may lead to adjacent fractures or cement leakage. In addition, the monomers in PMMA materials are toxic and have adverse effects on the cardiovascular and respiratory systems. Due to its biological inertness, it cannot promote bone integration and is difficult to remove screws during repair surgery.

[0004] In contrast, calcium phosphate cement (CPC) has attracted attention due to its similarity to natural bone. After curing, CPC can form a mineral similar to hydroxyapatite and spontaneously combine with bone tissue. However, CPC has the disadvantages of poor adhesion, insufficient mechanical properties, and lack of osteoinductivity, which limits its widespread application. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a high-strength bone cement and a preparation method and application thereof.

[0006] The present application provides a high-strength bone cement obtained by mixing a solid phase component and a liquid phase component at a solid-liquid ratio of 0.3 to 1 g / mL; The solid phase component specifically includes the following components in weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: Calcium dihydrogen phosphate monohydrate: calcium carbonate = 15-25: 20-40: 10-30: 10-30: 1-10: 1-10; The liquid phase component is selected from any one or more of a sodium chloride solution, a phosphate buffer solution, and a hydroxypropyl methylcellulose solution.

[0007] In response to the problem of insufficient anchor fixation strength during rotator cuff tear repair in patients with osteoporosis, the present application utilizes raw material components in a reasonable weight ratio as solid phase components, namely hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 15-25:20-40:10-30:10-30:1-10:1-10, and matches it with a specific liquid phase component to obtain a bone cement material with strong injectability, short curing time and excellent mechanical properties.

[0008] The present application aims to develop a high-strength calcium phosphate bone cement to enhance the anchor fixation effect in the repair of rotator cuff tears in osteoporotic patients. The calcium phosphate bone cement can form three-dimensional interconnected macropores, promote cell adhesion, improve the binding performance of the material with bone tissue, proliferate and increase the mechanical strength of the bone cement, enhance the anchor fixation strength, and meet the special needs of osteoporotic patients.

[0009] Preferably, the solid phase component specifically includes the following components in a weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 17-23: 25-35: 15-25: 15-25: 4-8: 3-9.

[0010] Preferably, the solid phase component specifically includes the following components in a weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 19:31:21:19:7:3.

[0011] Preferably, the tricalcium phosphate is selected from any one or more of α-tricalcium phosphate and β-tricalcium phosphate.

[0012] Preferably, the liquid phase component is selected from any one or more of a 0.7-1.1 wt% sodium chloride solution, a phosphate buffer solution with a pH of 7.2-7.4, and a 0.5-5 wt% hydroxypropyl methylcellulose solution.

[0013] Preferably, the liquid phase component is composed of a mixture of 0.7-1.1 wt% NaCl solution and 0.5-5 wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.5-1.5:0.5-1.5.

[0014] Preferably, the liquid phase component is composed of a mixture of 0.9 wt % NaCl solution and 1.5-3.5 wt % hydroxypropyl methylcellulose solution in a weight ratio of 0.5-0.8:1.2-1.5.

[0015] In a specific embodiment, the concentration of the NaCl solution may be 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, or 1.1 wt%.

[0016] In a specific embodiment, the concentration of the hydroxypropyl methylcellulose solution can be 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, or 5.0wt%.

[0017] In a specific embodiment, the weight ratio of the 0.9wt% NaCl solution to the 1.5-3.5wt% hydroxypropyl methylcellulose solution can be 0.5:0.5, 0.5:0.7, 0.5:0.8, 0.5:1.0, 0.5:1.2, 0.5:1.3, 0.5:1.5, 0.7:0.5, 0.7:0.8, 0.7:1.0, 0.7:1.2, 0.7:1.3, 0.7:1.5, 0.8:0.5, 0.8:0.7, 0.8:1.0, 0.8:1.2, 0.8:1.3, 0.8:1.5, 1.0:0.5, 1.0:0.7, 1.0:0.8, 1.0:1.2, 1.0:1.3, 1.0:1.5, 1.2:0.5, 1.2:0.7, 1.2:0.8, 1.2:1.0, 1.2:1.3, 1.2:1.5, 1.3:0.5, 1.3:0.7, 1.3:0.8, 1.3:1.0, 1.3:1.2, 1.3:1.5, 1.5:0.5, 1.5:0.7, 1.5:0.8, 1.5:1.0, 1.5:1.2, 1.5:1.3.

[0018] Through experimental analysis, it can be known that the present application utilizes the above-mentioned weight ratio of NaCl solution and hydroxypropyl methylcellulose solution to further improve the comprehensive performance of the bone cement material.

[0019] Preferably, the compressive strength of the high-strength bone cement is 11-25 MPa.

[0020] In a second aspect, the present application provides a method for preparing the above-mentioned high-strength bone cement, which specifically comprises the following steps in sequence: The raw materials in the solid phase component are fully mixed and uniformly, and the liquid phase component is added according to the solid-liquid ratio; then the two are mixed and stirred for 30s-80s, and then the mixture is filled into a syringe and then injected into a mold.

[0021] In a third aspect, the present application provides the use of the above-mentioned high-strength bone cement in the preparation of bone repair materials.

[0022] In summary, the technical solution of this application has the following effects: The present application obtains a bone cement material with strong injectability, short curing time and excellent mechanical properties by utilizing raw material components in a reasonable weight ratio as solid phase components, namely, hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: monocalcium phosphate monohydrate: calcium carbonate = 15-25:20-40:10-30:10-30:1-10:1-10, and matching them with specific liquid phase components.

[0023] The present application further improves the comprehensive performance of bone cement materials by screening and optimizing the dosage ratio of solid phase components and the types of liquid phase components. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are the straight disc-shaped high-strength bone cement samples and cylindrical high-strength bone cement samples prepared in the performance testing experiment. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example

[0026] Examples 1-5 Examples 1-5 respectively provide a high-strength bone cement and a preparation method thereof.

[0027] The difference between the above embodiments is that the weight ratios of the components in the high-strength bone cement are different, as specifically shown in Table 1.

[0028] The preparation method of the high-strength bone cement in the above embodiment is: According to Table 1, the raw materials in the solid phase component are fully mixed according to the corresponding weight ratio, and 70g of the solid phase component is added to 100mL of the liquid phase component (composed of a mixture of 0.9wt% NaCl solution and 2.5wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.7:1.3) according to the solid-liquid ratio of 0.7g / mL; then the two are mixed and stirred for 60s, and then the solid-liquid mixture is filled into a syringe, and then injected into a mold to obtain; wherein the tricalcium phosphate is α-tricalcium phosphate.

[0029] Table 1 Weight ratio of each component in high strength bone cement in Examples 1-5 Embodiment 6-15 Examples 6-15 respectively provide a high-strength bone cement and a preparation method thereof.

[0030] The difference between the above embodiment and embodiment 1 is that the types of liquid phase components are different, as shown below.

[0031] In Example 6: the liquid phase component is 0.9wt% NaCl solution.

[0032] In Example 7: the liquid phase component is composed of a 2.5 wt% hydroxypropyl methylcellulose solution mixture.

[0033] In Example 8: the liquid phase component is composed of a mixture of 0.9wt% NaCl solution and phosphate buffer solution with a pH value of 7.2 in a weight ratio of 0.7:1.3.

[0034] In Example 9: the liquid phase component is composed of a mixture of 0.9 wt % NaCl solution and 10 wt % hydroxypropyl methylcellulose solution in a weight ratio of 0.7:1.3.

[0035] In Example 10: the liquid phase component is composed of a mixture of a phosphate buffer solution with a pH value of 7.2 and a 2.5 wt % hydroxypropyl methylcellulose solution in a weight ratio of 0.7:1.3.

[0036] In Example 11: the liquid phase component is composed of a mixture of 2.5 wt% hydroxypropyl methylcellulose solution and 0.9 wt% NaCl solution in a weight ratio of 10:1.

[0037] In Example 12: the liquid phase component is composed of a mixture of 0.9 wt% NaCl solution and 2.5 wt% hydroxypropyl methylcellulose solution in a weight ratio of 1.3:0.7.

[0038] In Example 13: the liquid phase component is composed of a mixture of 0.9 wt% NaCl solution and 2.5 wt% hydroxypropyl methylcellulose solution in a weight ratio of 1.5:0.5.

[0039] In Example 14: the liquid phase component is composed of a mixture of 0.9 wt% NaCl solution and 2.5 wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.5:1.5.

[0040] In Example 15: the liquid phase component is composed of a mixture of 0.9 wt% NaCl solution and 2.5 wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.8:1.2.

[0041] The other process parameters in the above embodiment are the same as those in embodiment 1.

[0042] Comparative Example Comparative Examples 1-4 Comparative Examples 1-4 respectively provide a high-strength bone cement and a preparation method thereof.

[0043] The difference between the comparative example and Example 1 is that the weight ratio or composition of the components in the high-strength bone cement is different, as shown below.

[0044] In Comparative Example 1: the solid phase component is composed of the following components in the weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate = 19:31:21:19.

[0045] In Comparative Example 2: the solid phase component is composed of the following components in the following weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: monocalcium phosphate monohydrate: octacalcium phosphate = 19:31:21:19:9:11.

[0046] In Comparative Example 3: the solid phase component is composed of the following components in the following weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: monocalcium phosphate monohydrate: calcium carbonate = 30:17:7:32:0.5:17.

[0047] In Comparative Example 4: the solid phase component is composed of the following components in the weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 11:45:8:7:17:0.5.

[0048] Performance testing (1) Injectability The solid-liquid mixture prepared in the embodiment and the comparative example according to the solid-liquid ratio was filled into a 10 mL disposable syringe, which was placed vertically on a mechanical testing machine plate, and the solid-liquid mixture was pushed out by injection at a rate of 10 mm / min until the maximum propulsion force reached 100 N. The percentage of the injected bone cement mass to the total mass of the bone cement before injection was recorded as the injectability, and the results are shown in Table 1.

[0049] (2) Curing time The solid-liquid mixture prepared in the embodiment and the comparative example according to the solid-liquid ratio was filled into a 10 mL disposable syringe and then injected into a mold to obtain a disc-shaped high-strength bone cement sample (such as Figure 1 The samples were placed in an environment with a temperature of 37°C and a relative humidity of 100% and the curing time of the samples was tested according to the standard ISO / DIS18531.

[0050] (3) Compression strength The solid-liquid mixture prepared in the embodiment and the comparative example according to the solid-liquid ratio was filled into a 10 mL disposable syringe and then injected into a mold to obtain a disc-shaped high-strength bone cement sample (such as Figure 1 As shown), the samples were placed in an environment with a temperature of 37°C and a relative humidity of 100%. After curing for 24 hours and 96 hours, the compressive strength of the samples was tested according to the standard ISO / DIS18531.

[0051] The solid-liquid mixture prepared in the embodiment and the comparative example according to the solid-liquid ratio was filled into a 10 mL disposable syringe, and then injected into a mold to obtain a cylindrical high-strength bone cement sample (such as Figure 1 As shown), the bone cement was placed in an environment with a temperature of 37°C and a relative humidity of 100%. After curing for 96 hours, the bone cement was immersed in SBF simulated body fluid after curing for 96 hours. The liquid was changed every 3 days. After 9 days, the bone cement was taken out and dried, and the compression strength of the sample was tested.

[0052] Test results: as shown in Table 2.

[0053] Table 2 Performance test results of high strength bone cement in the examples and comparative examples Combined with Table 2, by comparing the performance test results of bone cement in the embodiments and the comparative examples, it can be seen that the present application uses raw material components in a reasonable weight ratio as solid phase components, namely hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 15-25: 20-40: 10-30: 10-30: 5-15: 5-15, and matches it with a specific liquid phase component to obtain a bone cement material with strong injectability, short curing time and excellent mechanical properties.

[0054] By comparing the test results of Examples 1-5, it can be seen that the solid phase components in Comparative Example 1 are composed of the following weight ratios: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate = 19:31:21:19, and the solid phase components in Comparative Example 2 are composed of the following weight ratios: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: monocalcium phosphate monohydrate: octacalcium phosphate = 19:31:21:19:9:11, and the prepared bone cement material has poor injectability, a long curing time, and a weak compression strength. The solid phase components in Comparative Example 3 are composed of the following weight ratios: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: monocalcium phosphate monohydrate: calcium carbonate = 30:17:7:32:0.5:17, and the prepared bone cement material has a long curing time and a weak compression strength. In comparative example 4, the solid phase components are composed of the following weight ratios: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 11:45:8:7:17:0.5, and the compression strength of the prepared bone cement material is weak. In contrast, the solid phase components of the present application are specifically controlled to include the following weight ratios: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 17-23:25-35:15-25:15-25:3-9:4-8, which further improves the comprehensive performance of the bone cement material.

[0055] By comparing the test results of Example 1 with those of Examples 6-15, it can be seen that the present application selects a liquid phase component composed of a mixture of 0.7-1.1wt% NaCl solution and 0.5-5wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.5-1.5:0.5-1.5, which further improves the comprehensive performance of the bone cement material.

[0056] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A high-strength bone cement, characterized in that: It is obtained by mixing the solid phase component and the liquid phase component at a solid-liquid ratio of 0.3-1 g / mL; The solid phase component specifically includes the following components in a weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 15-25: 20-40: 10-30: 10-30: 1-10: 1-10; The liquid phase component is selected from any one or more of a sodium chloride solution, a phosphate buffer solution, and a hydroxypropyl methylcellulose solution.

2. The high-strength bone cement according to claim 1, characterized in that: The solid phase component specifically includes the following components in a weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 17~23: 25~35: 15~25: 15~25: 4~8: 3~9.

3. The high-strength bone cement according to claim 2, characterized in that: The solid phase component specifically includes the following components in a weight ratio: hydroxyapatite: tricalcium phosphate: tetracalcium phosphate: disodium hydrogen phosphate: calcium dihydrogen phosphate monohydrate: calcium carbonate = 19:31:21:19:7:

3.

4. The high-strength bone cement according to claim 1, characterized in that: The tricalcium phosphate is selected from any one or more of α-tricalcium phosphate and β-tricalcium phosphate.

5. The high-strength bone cement according to claim 1, characterized in that: The liquid phase component is selected from any one or more of a 0.7-1.1wt% sodium chloride solution, a phosphate buffer solution with a pH value of 7.2-7.4, and a 0.5-5wt% hydroxypropyl methylcellulose solution.

6. The high-strength bone cement according to claim 1, characterized in that: The liquid phase component is composed of a mixture of a 0.7-1.1wt% NaCl solution and a 0.5-5wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.5-1.5:0.5-1.

5.

7. The high-strength bone cement according to claim 6, characterized in that: The liquid phase component is composed of a mixture of a 0.9wt% NaCl solution and a 1.5-3.5wt% hydroxypropyl methylcellulose solution in a weight ratio of 0.5-0.8:1.2-1.

5.

8. The high-strength bone cement according to claim 1, characterized in that: The compressive strength of the high-strength bone cement is 11-25 MPa.

9. The method for preparing high-strength bone cement according to any one of claims 1 to 8, characterized in that: Specifically, the following steps are performed in sequence: The raw materials in the solid phase component are fully mixed and uniformly, and the liquid phase component is added according to the solid-liquid ratio; then the two are mixed and stirred for 30s-80s, and then the mixture is filled into a syringe and then injected into a mold.

10. Use of the high-strength bone cement according to any one of claims 1 to 8 in the preparation of bone repair materials.